Excess Mortality for Abdominal Aortic Aneurysms and the Potential of Strict Implementation of Cardiovascular Risk Management: A Multifaceted Study Integrating Meta-Analysis, National Registry, and PHAST and TEDY Trial Data. (March 2023) - Tomee, Stephanie M.; Bulder, Ruth M.A.; Meijer, C. Arnoud; van Berkum, Ingrid; Hinnen, Jan-Willem; Schoones, Jan W.; Golledge, Jonathan; Bastiaannet, Esther; Matsumura, Jon S.; Hamming, Jaap F.; Hultgren, Rebecka; Lindeman, Jan H.
Abstract : Objective: Previous studies imply a profound residual mortality risk following successful abdominal aorta aneurysm (AAA) repair. This excess mortality is generally attributed to increased cardiovascular risk. The aim of this study was (1) to quantify the excess residual mortality for patients with AAA, (2) to evaluate the cross sectional level of cardiovascular risk management, and (3) to estimate the potential of optimised cardiovascular risk management to reduce the excess mortality in these patients. Methods: Excess mortality was estimated through a systematic review and meta-analysis, and through data from the Swedish National Health Registry. Cardiovascular risk profiles were individually assessed during eligibility screening of patients with AAA for two multicentre pharmaceutical AAA stabilisation trials. The potential of full implementation of cardiovascular risk management was estimated through the validated Second Manifestations of ARTerial disease (SMART) risk scores algorithm. Results: The meta-analysis showed a similarly impaired survival for patients who received early repair (small AAA) or regular repair (≥ 55 mm), and a further impaired survival for patients under surveillance for a small AAA. Excess mortality was further quantified using Swedish population data. The data revealed a more than quadrupled and doubled five year mortality rate for women and men who had their AAA repaired, respectively. Evaluation of the level of risk management of 358 patients under surveillance in 16 Dutch hospitals showed that the majority of patients with AAA did not meet therapeutic targets set for risk management in high risk populations, and indicated a more pronounced prevention gap in women. Application of the SMART risk score algorithm predicted that optimal implementation of risk management guidelines would reduce the 10 year risk of major adverse cardiovascular events from 43% to 14%. Conclusion: Independent of the rupture risk, AAA is associated with a worryingly compromised life expectancy with a particularly poor prognosis for women. Optimal implementation of cardiovascular risk prevention guidelines is predicted to profoundly reduce cardiovascular risk.